Free‐Breathing Volumetric Liver R2 and Proton Density Fat Fraction Quantification in Pediatric Patients Using Stack‐of‐Radial MRI With Self‐Gating Motion Compensation - Zhong, Xiaodong; Hu, Houchun H.; Armstrong, Tess; Li, Xinzhou; Lee, Yu‐Hsiu; Tsao, Tsu‐Chin; Nickel, Marcel D.; Kannengiesser, Stephan A.R.; Dale, Brian M.; Deshpande, Vibhas; Kiefer, Berthold; Wu, Holden H. (Journal of magnetic resonance imaging, 2021)
Background Stack‐of‐radial multiecho gradient‐echo MRI is promising for free‐breathing liver R2* quantification and may benefit children. Purpose To validate stack‐of‐radial MRI with self‐gating motion compensation in phantoms, and to evaluate it in children. Study Type Prospective. Phantoms Four vials with different R2* driven by a motion stage. Subjects Sixteen pediatric patients with suspected nonalcoholic fatty liver disease or steatohepatitis (five females, 13 ± 4 years, body mass index 29.2 ± 8.6 kg/m2). Field Strength/Sequences Stack‐of‐radial, and 2D and 3D Cartesian multiecho gradient‐echo sequences at 3T. Assessment Ungated and gated stack‐of‐radial proton density fat fraction (PDFF) and R2* maps were reconstructed without and with self‐gating motion compensation. Stack‐of‐radial R2* measurements of phantoms without and with motion were validated against reference 2D Cartesian results of phantoms without motion. In subjects, free‐breathing stack‐of‐radial and reference breath‐hold 3D Cartesian were acquired. Subject inclusion for statistical analysis and region of interest placement were determined independently by two observers. Statistical Tests Phantom results were fitted with a weighted linear model. Demographic differences between excluded and included subjects were tested by multivariate analysis of variance. PDFF and R2* measurements were compared using Bland–Altman analysis. Interobserver agreement was assessed by the intraclass correlation coefficient (ICC). Results Ungated stack‐of‐radial R2* inside moving phantom vials showed a significant positive bias of 64.3 s−1 (P < 0.00001), unlike gated results (P > 0.31). Subject inclusion decisions for statistical analysis from two observers were consistent. No significant differences were found between four excluded and 12 included subjects (P = 0.14). Compared to breath‐hold Cartesian, ungated and gated free‐breathing stack‐of‐radial exhibited mean R2* differences of 18.5 s−1 and 3.6 s−1. Mean PDFF differences were 1.1% and 1.0% for ungated and gated measurements, respectively. Interobserver agreement was excellent (ICC for PDFF = 0.99, ICC for R2* = 0.90; P < 0.0003). Data Conclusion Stack‐of‐radial MRI with self‐gating motion compensation seems to allow free‐breathing liver R2* and PDFF quantification in children. Level of Evidence 2 Technical Efficacy Stage 2